Challenges in the Utilization of Technology-Based Administration Services by the Community in Tongke-Tongke Village, East Sinjai District - Amalia, Husnul; Takdir, Muhammad; Wahid, Abd (Prodi Ilmu Pemerintahan, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Pattimura, 2025)
This study aims to analyze the capacity of the community in utilizing technology-based administrative services. The method used is a qualitative research method. The results of the study show that the capacity of the people of Tongke-Tongke Village in general has shown the ability to adopt technology-based administrative services. This can be seen from four main indicators, namely knowledge, skills, awareness, and attitude. In terms of knowledge, most of the younger generation has understood the concept and benefits of digital administration services, although adults and the elderly are still limited in their understanding. In terms of skills, access to devices such as smartphones is quite adequate, but the ability to operate technology is still uneven, especially for people over 40 years old who still need assistance. In terms of awareness, both the community and village officials are beginning to realize the importance of digitizing services as an effort to improve the efficiency and ease of service, although limited socialization has made this awareness not reach all levels of society. Meanwhile, in terms of attitudes, the community and village officials generally show an open and positive attitude towards changes towards a digital system, and have a willingness to learn and follow developments. Overall, the people of Tongke-Tongke Village in general have been able to adopt technology-based administrative services, but further efforts are still needed in the form of training, socialization, and mentoring so that all community groups can participate optimally and equally. The findings of the study show the importance of routine socialization, increasing people's digital literacy. By utilizing the results of this research, the village government can develop a more appropriate strategy to optimize technology-based services to be more effective, efficient, and reach all levels of society.